Development and Integration of GeoGebra Applets in Mathematics Learning - Siregar, Hesty Marwani; Nurjanah, Nurjanah; Nuraeni, Reni (Pedagonal : Jurnal Ilmiah Pendidikan, 2024)
Mathematics is a material that students consider difficult because its concepts are abstract. To overcome this, one approach that can be used is using technology-assisted learning. GeoGebra applet is a technology that is commonly used in mathematics. However, a few studies have discussed the relevance of this study to further research related to GeoGebra applets in mathematics and explore its potential. Therefore, this article discusses the development and integration of GeoGebra Applets in Mathematics Learning. The aim of this research is to investigate the relevance of the study to further research related to GeoGebra applets in mathematics and discuss the potential of these applets in enhancing students’ ability in mathematics learning. The research method used is the Systematic Literature Review method, which analyses articles from 2013 to 2022. The research results show that GeoGebra Applets have been developed in various forms, including applications, ebooks, and assignment applications. The most commonly discussed learning material is geometry, with the potential for further research on other materials. GeoGebra Applets have been proven to help improve students' understanding, representation, problem-solving, and critical and spatial thinking skills in mathematics learning. This application positively contributes to the quality of mathematics learning through various forms of learning, including independent, direct, and innovative learning.